2012
DOI: 10.1038/leu.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacitidine in aggressive myelodysplastic syndromes regulates chromatin structure at PU.1 gene and cell differentiation capacity

Abstract: Epigenetic 5-azacitidine (AZA) therapy of high-risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) represents a promising, albeit not fully understood, approach. Hematopoietic transcription factor PU.1 is dynamically regulated by upstream regulatory element (URE), whose deletion causes downregulation of PU.1 leading to AML in mouse. In this study a significant group of the high-risk MDS patients, as well as MDS cell lines, displayed downregulation of PU.1 expression within CD34 þ cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…The most common APA-related adverse events were hematologic toxicities grade 1-4 (Table 1) Combined transcriptional targeting by PPARγ and RAR ligands as well as AZA treatment have been shown to induce myeloid differentiation and to attenuate leukemia cell growth. 4,[9][10][11] The induction of molecular CR, strong myeloid differentiation in leukemia blasts ( Figure 1C) and in residual hematopoiesis ( Figure 1B and data not shown) during APA treatment emphasizes our hypothesis that combined biomodulation with APA might act synergistically on leukemic differentiation and growth control. Previous data had already suggested that metronomic biomodulatory therapy approaches differentially target hallmarks of cancer, i.e.…”
Section: Biomodulatory Therapy Induces Complete Molecular Remission Imentioning
confidence: 73%
“…The most common APA-related adverse events were hematologic toxicities grade 1-4 (Table 1) Combined transcriptional targeting by PPARγ and RAR ligands as well as AZA treatment have been shown to induce myeloid differentiation and to attenuate leukemia cell growth. 4,[9][10][11] The induction of molecular CR, strong myeloid differentiation in leukemia blasts ( Figure 1C) and in residual hematopoiesis ( Figure 1B and data not shown) during APA treatment emphasizes our hypothesis that combined biomodulation with APA might act synergistically on leukemic differentiation and growth control. Previous data had already suggested that metronomic biomodulatory therapy approaches differentially target hallmarks of cancer, i.e.…”
Section: Biomodulatory Therapy Induces Complete Molecular Remission Imentioning
confidence: 73%
“…For example, Aza-dC facilitates tumor necrosis factor alpha-induced monocytic differentiation of two AML cell lines NB4 and U937 by demethylation of DIF2 (also known as IER3) promoter and thus up-regulation of the gene [60] . Similarly, an upstream regulatory element within PU.1 promoter has been shown to be demethylated by Aza leading to an upregulation of PU.1 and its target genes [61] . Co-treatment of CD34 + cells derived from MDS patients by Aza and granulocyte colony-stimulating factor led to myeloid differentiation [61] .…”
Section: Inhibition Of Dnmts By Aza-dcmentioning
confidence: 99%
“…Similarly, an upstream regulatory element within PU.1 promoter has been shown to be demethylated by Aza leading to an upregulation of PU.1 and its target genes [61] . Co-treatment of CD34 + cells derived from MDS patients by Aza and granulocyte colony-stimulating factor led to myeloid differentiation [61] . Another study has shown that AzadC induces expression of olfactomedin 4 (OLFM4), of which an over-expression led to apoptosis and differentiation HL60 cell line [62] .…”
Section: Inhibition Of Dnmts By Aza-dcmentioning
confidence: 99%
“…In line with the observation that 5-aza-cytidine may promote the differentiation of malignantly transformed cells by inducing the reexpression of epigenetically downregulated PU.1 36 and considering the crucial role that PU.1 plays in the regulation of NK-cell differentiation and homeostasis, 37 we assume that the re-expression of PU.1 might have promoted NK-cell differentiation in our model. In addition, it has been shown for low (but not high dose) 5-aza-cytidine therapy that this may increase the number of cells in the S phase, and may thus promote cell-cycle progression.…”
Section: /Cd19mentioning
confidence: 48%